KONJUNGTOR KOORDINATIF DAN SUBORDINATIF DALAM PEMBELAJARAN MENULIS NARASI MAHASISWA - Munawwar (Jurnal Pendidikan Sang Surya, 2023)
This research aims to describe errors in the use of coordinating and subordinating conjunctions in student narratives as assignments in the Writing course. This research is of a qualitative type, using qualitative descriptive methods to describe errors in the use of conjunctions in the narratives of Tomakaka University students. The data for this research is in the form of narrative writing, while the data source is obtained from a collection of assignments that have been collected in the Writing course. Data collection techniques use documentation techniques. The instrument of this research is the researcher himself. The data analysis technique in this research uses descriptive analysis by analyzing errors in using conjunctions and describing them in sentences. The research results show errors in the use of coordinating conjunctions, namely and, but, and whereas.